PERANAN TERAPI INSULIN INTENSIF TERHADAP INTERLEUKIN-6 (IL-6) DAN LUARAN KLINIK PADA PENDERITA KRITIS DENGAN HIPERGLIKEMIA - Wiryana, Made (journal of internal medicine; Vol. 9, No. 2 Mei 2008, 2012)
Hiperglycemia and insulin resistance are common in critically ill patients, even that have not previously had diabetes. Though it has been reported that pronounced hyperglycemia may lead to complications in such patients and cause of reactive oxygen species (ROS) production, although data from controlled trial are still lacking. The debatable issue focused on whether intensive insulin therapy to normalized blood glucose improves prognosis. The debate is mainly about the time to start therapy, and target of blood glucose level. The main purpose of this research is to know the different between intensive insulin therapy and conventional insulin therapy on decreases of cytokine production (IL-6), increase of albumin level and event of systemic inflammatory respons syndrome (SIRS). The design of this study is randomized pre and post control group design involving 40 adult patients that admitted to the ICU Sanglah hospital Denpasar. They were randomly assigned to receive intensive insulin therapy in which blood glucose at the level between 80 ? 110 mg/dL or conventionl insulin therapy in which insulin therapy start if the blood glucose level exceed 215 mg/dL and blood glucose maintained at the level between 180 ? 200 mg/dL. The results of this study showed that: (1) Significant decrease of IL-6 level (10.25 vs 2.02; p=0.023); (2) Significant increase of albumin level (0.62 vs 0.22); (3) Significant decrease of SIRS (10 % vs 45%, p=0.000) on intensive insulin therapy group compare to the conventional insulin therapy group. Conclusions of this study is that the increase insulin dose as well as intensive insulin therapy can maintain blood glucose level at the level normoglycaemia between 80-110 mg/dL faster compare to the conventional insulin therapy. On the otherhand, interleukin-6 decreases cause of decreases ROS production and anti inflammatory effect of insulin. Intensive insulin therapy can increase albumin level and decrease of SIRS event on hyperglycemia in critically ill ICU patients compare to the conventional insulin therapy.
Keywords: hyperglicemia, intensive insulin therapy, critically ill patients, pro-inflammatory cytokine, albumin, SIRS